Gene editing therapy as a therapeutic approach for cardiovascular diseases in animal models: A scoping review - Quan Duy Vo (PLoS ONE, 2025)
Background Cardiovascular diseases (CVDs) are the leading cause of mortality worldwide, with hereditary genetic factors contributing substantially to disease burden. Current treatments, including lifestyle modifications, pharmacotherapy, and surgical interventions, focus primarily on symptom management but fail to address underlying genetic causes, often resulting in disease progression or recurrence. Gene therapy has emerged as a transformative approach, offering a potential treatment. This review explores its efficacy and safety in animal models, identifying opportunities for future advancements. Methods This review investigated studies on gene editing interventions in animal models of CVDs, retrieved from PubMed, ScienceDirect, and Web of Science up to December 2024. Result A total of 57 studies were included in this review. Mice (86%) were the predominant model, with CRISPR-Cas9 (53%) and AAV vectors (80%) as the most used tools. Key targets included PCSK9 (32%), LDLR (9%), and MYH6/7 (7%), achieving 25–85% editing efficiency in liver/heart tissues. Base editors (ABE/CBE) showed superior safety, with <1% off-targets versus CRISPR-Cas9’s 2–5 off-targets per guide. Reported toxicity risks included liver injury (AAVs, 23%) and transient cytokine elevation (LNPs, 14%). Conclusion Gene editing therapy shows great potential for treating CVDs, with high efficiency, strong therapeutic outcomes, and favorable safety in animal models. Continued innovation and rigorous evaluation could transform cardiovascular treatment, benefiting patients with untreatable conditions.